Synthesis of Heavy Dicyanamide Homologues from Air‐Stable Precursors. Issue 55 (7th September 2018) - Binder, Justin F.; Kosnik, Stephanie C.; St Onge, P. Blake J.; Macdonald, Charles L. B.
Abstract: A convenient synthesis of dicyanophosphide and dicyanoarsenide anions is reported. These heavy homologues of the long‐known and fundamentally important dicyanamide anion were formed through the nucleophilic displacement of bis(diphenylphosphino)ethane (dppe) from the pnictogen + transfer agents [dppePn][BPh4 ] (Pn=P, As) by exposure to cyanide salts. The protocol requires three synthetic steps from commercially available materials and the [dppePn][BPh4 ] salts are remarkably temperature, air, and moisture stable. All products have been fully characterized by spectroscopic methods and by single‐crystal X‐ray diffraction, and the electronic structures of the DCPn anions have been assessed computationally. Abstract : A convenient synthesis of dicyanophosphide and dicyanoarsenide anions is reported. These heavy homologues of dicyanamide were synthesized using the readily prepared and air‐stable Pn + transfer agents [dppePn][BPh4 ] (Pn=P, As), and characterized using spectroscopic, crystallographic, and computational methods.